Interaction Architectures to Strengthen Belonging: Hybrid Workers in Digital Marketing Agencies - Bombín Marrodán, Adriana; Llovet Rodríguez, Carmen (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This article analyses how interaction architectures influence the sense of belonging and engagement of hybrid employees in digital marketing agencies in Spain. Through in-depth interviews with managers and a review of the literature on internal marketing and belonging, it was identified that the most used tools mainly serve an informational function. These include platforms such as Discord and Slack, newsletters, celebrations, training and meetings, all aimed at strengthening the emotional connection that characterizes internal marketing. The results show that these practices contribute to strengthening cultural and emotional ties in hybrid environments. However, companies face key challenges in consolidating a sense of belonging, including technological barriers and the difficulty of integrating organizational culture into the digital environment. The study offers guidelines for designing effective strategies to strengthen internal cohesion in the digital age.